Hilbert transform of FFT pruned cross correlation function for optimization in time delay estimation - Noor Shafiza, Mohd Tamim; Farid, Ghani (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/